Highly luminescent silver nanocluster-doped fluorophosphate glasses for microfabrication of 3D waveguides. Issue 88 (11th December 2017) - Fares, H.; Santos, S. N. C.; Santos, M. V.; Franco, D. F.; Souza, A. E.; Manzani, D.; Mendonça, C. R.; Nalin, M.
Abstract : Highly photoluminescent glasses were prepared by embedding silver nanoclusters (Ag NCs) in a fluorophosphate matrix using a melt-quenching method. Abstract : Highly photoluminescent glasses were prepared by embedding silver nanoclusters (Ag NCs) in a fluorophosphate matrix using a melt-quenching method. The NCs sizes were varied through silver concentration and thermal annealing. Depending on the NC size and excitation wavelength, different colors can be generated ranging from blue to yellow. The tunable photoluminescence and the excellent stability of Ag NCs even after heat treatment are attractive features for photonic applications. In this sense, we demonstrated the fabrication of luminescent tridimensional waveguides in as-prepared glasses by femtosecond laser micromachining. The waveguides were found to emit and guide white light when excited at 325 nm. We foresee that this study presents promising results for the development of new photonic devices and data storage.